The future of Asian trade deals and IP - LIU, Kung-Chung (Institutional Knowledge at Singapore Management University, 2019)
The pulling out of the Trans-Pacific Partnership (TPP) by the US marks a new era for trade deals and potentially for intellectual property (IP). The TPP has evolved to become the Comprehensive and Progressive Agreement for TPP (CPTPP) with the remaining 11 members suspending some of its provisions, over half of which are IP-related. While the TPP excludes the two Asian giants – India and the People's Republic of China (PRC) – the ongoing Regional Comprehensive Economic Partnership (RCEP) negotiations include both of them.The first part of this edited collection sets out to re-examine some basic principles of trade negotiation, such as choosing the right representatives to negotiate and enhancing transparency as a cure to the public's distrust against trade talks; moreover, it analyses how CPTPP might impact on RCEP's IP chapter and examines the possible norm setters of Asian IP. It then focuses on the PRC's trade and IP strategy against the backdrop of the power games between the PRC, India and the US.The second part of the book reflects on issues related to investor–state dispute settlement and its relationship with IP, such as how to re-calibrate the balance in international investment arbitration, and whether compulsory license of IP constitutes expropriation in India, the PRC and select ASEAN countries.The third part of the book questions and strives to improve some of the proposed IP provisions of CPTPP and RCEP and to redefine some aspects of international IP norms, such as: pre-grant patent opposition and experimental use exception; patent term extension; patent linkage and data exclusivity for the pharmaceutical sector; plant variety protection; pre-established damages for copyright infringement; and the restructuring of copyright limitations in the public interest.